(99m)Tc-DPD scintigraphy and SPECT/CT in patients with AL and ATTR type amyloidosis: Potential clinical implications - Lee, Joohee (Medicine (Baltimore), 2020)
Although pathological confirmation is the gold standard for diagnosis of amyloidosis, there is a need for a relevant imaging modality to identify involved organs and evaluate disease extent. Thus, we prospectively investigated imaging findings of (99m)Tc-DPD scintigraphy in AL and ATTR amyloidosis. A total of 21 subjects with pathologically confirmed AL or ATTR amyloidosis were included. Pretreatment whole body (99m)Tc-DPD planar scanning and regional SPECT/CT were performed in all subjects. For allegedly involved organs, (99m)Tc-DPD uptake was visually and semi-quantitatively evaluated on a 4-point scale (grade 0: no uptake, 1: uptake less than spine, 2: uptake similar to spine, and 3: uptake greater than spine). There were 29 organs involved in AL and 12 in ATTR. Significant (99m)Tc-DPD uptake was found in 24 organs (sensitivity = 82.8%) in AL and 9 organs (sensitivity = 75.0%) in ATTR. Additional SPECT/CT was helpful to ensure abnormal DPD uptake in the involved organs, which was uncertain by attenuation in planar imaging. Degree of (99m)Tc-DPD uptake was significantly higher in ATTR compared with AL amyloidosis (P = .017). Diffuse soft tissue uptake with photon defects in the liver area was found only in ATTR amyloidosis. This study showed that (99m)Tc-DPD scintigraphy might have capacity to differentiate between AL and ATTR subtypes with good sensitivity in various organs involving primary systemic AL and ATTR amyloidosis. Additional SPECT/CT significantly improved the diagnostic efficacy of (99m)Tc-DPD scintigraphy.